Mediating Role of Self-Efficacy on the effect of social support and Employee Burnout when Working from Home (WFH) - Solicha; Murniasih, Farhanah; Febriyani, Lavirni Salma (Faculty of Psychology, Universitas Medan Area, 2024)
Working from home (WFH) is considered beneficial in increasing productivity as it reduces the need to travel. However, WFH also has potential risks to mental health, such as burnout. This study aims to analyze the mediating role of self-efficacy in the relationship between social support and burnout in employees who do WFH. This research design uses quantitative, with a sample of 255 respondents who are dominated by women aged 18-30 years. The sampling technique used purposive sampling. Data collection used three questionnaires consisting of General Self-Efficacy Scale (Schwarzer & Jerusalem, 1995), Maslach Burnout Inventory General Survey (Maslach et al., 1996) and Social Support Scale adapted by Prijayanti (2015). Data analysis was conducted using Hayess' PROCESS Mediation Model. The results show that social support significantly affects burnout and self-efficacy significantly mediates the relationship between social support and burnout in employees working WFH. This finding confirms the importance of self-efficacy as a key mechanism that enables individuals to utilize existing social support to reduce the risk of burnout in WFH settings.